2017
DOI: 10.1177/1558944717715105
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Complications of Percutaneous Fixation of Hand Fractures in a Procedure Room Versus the Operating Room

Abstract: Metacarpal and phalanx fractures of the hand amendable to closed reduction and percutaneous pinning can be treated in the procedure room with no increase in risk of infection, malunion, or nonunion rates. In addition, these surgeries can be performed in a procedure room with lower cost and less charges to patients than in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“… 18 When CTR cases were analyzed, they demonstrated even lower infection rates in the office, with an incidence of only 0.56%. This agrees with the multiple other studies that have shown no increase in infection rates when compared with the traditional OR 9 , 19 despite the OPR population being older with more comorbidities.…”
Section: Discussionsupporting
confidence: 92%
“… 18 When CTR cases were analyzed, they demonstrated even lower infection rates in the office, with an incidence of only 0.56%. This agrees with the multiple other studies that have shown no increase in infection rates when compared with the traditional OR 9 , 19 despite the OPR population being older with more comorbidities.…”
Section: Discussionsupporting
confidence: 92%
“…Certain hand procedures have shifted toward management in the outpatient clinic setting as opposed to the OR. Specifically with regard to hand fractures, fixation in a procedure room is associated with lower cost and charges to patients and no difference in rate of postoperative infection, malunion, or nonunion 8. In a retrospective review, open carpal tunnel release under local anesthesia in a procedure room setting minimized direct surgical costs compared to the operating room or other modes of anesthesia 26.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that field sterility for simple (nonpermanent implant) hand operations, including closed K-wire fixation, yields low, acceptable infection rates with minimal patient morbidity. [50][51][52][53][54][55][56][57][58] When antibiotics such as cephalosporins are required, they can be given orally with 90% of the bioavailability of the intravenous route. 59,60 Although an exhaustive list of procedures cannot cover all possibilities, Table 4 illustrates broadly some of…”
Section: Safety Of Field Sterility Versus Full Sterilitymentioning
confidence: 99%